2021
DOI: 10.18488/journal.1.2021.114.200.208
|View full text |Cite
|
Sign up to set email alerts
|

Social Learning of Fear: An Investigation of Foreign Language Learning Anxiety

Abstract: Fear of foreign language learning can stem from the learners, the instructors and also the activities planned. Learners learning anxiety can be increased or decreased depending on the learning environment they are in. Instructors play an important role to allow maximum learning to take place. Activities planned for language learning can facilitate or hinder learning. This study investigates the fear of foreign language learning among undergraduates. The instrument is rooted from Horwitz (1986) survey on Foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To address motivation issues, Ibrahim et al (2023) recommended increasing student motivation in language classrooms by creating interesting coursework, authentic lesson plans, meaningful activities, and relevant tests. In a related context, Rahmat et al (2021) emphasized the importance of examining students' perspectives on a variety of interaction activities, including small group interactions, paired communication activities, and additional scaffolding activities to support people with higher levels of anxiety. On the other hand, Djafri and Wimbarti (2018) suggested that foreign language teachers improve their teaching methods and behaviours to create a more conducive environment and reduce language anxiety.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…To address motivation issues, Ibrahim et al (2023) recommended increasing student motivation in language classrooms by creating interesting coursework, authentic lesson plans, meaningful activities, and relevant tests. In a related context, Rahmat et al (2021) emphasized the importance of examining students' perspectives on a variety of interaction activities, including small group interactions, paired communication activities, and additional scaffolding activities to support people with higher levels of anxiety. On the other hand, Djafri and Wimbarti (2018) suggested that foreign language teachers improve their teaching methods and behaviours to create a more conducive environment and reduce language anxiety.…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Findings reveal that the communication apprehension that students portray, can lead to a fear of tests, negative evaluations, and even foreign language classes. Rahmat et al (2021) continued to further explore this the following year as well. Their study investigated the fear of foreign language learning among undergraduates, examining factors related to learners, instructors, and planned activities.…”
Section: Past Studies On Fear Of Learning a Foreign Languagementioning
confidence: 99%